Antidepressant-like effects of modulating light: dark cycle on female wistar rats in the forced swim test - Karslı, T. Alper. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 2002., 2002)
This study attempts to examine British ways of viewing, depicting and evaluating Ottoman architecture and design in the light of prevailing methodology of criticism and architectural culture of the period. As shown in the study, during the nineteenth century, the expertise in the field of architectural criticism was more developed and the actual application of design and architectural styles of non-European countries were experimented more frequently than in the previous centuries. As a result of the study, it emerges that British approaches to the Oriental/Islamic and Ottoman visual arts were not always uniform and monolithic, depending on the individual views and backgrounds of the artists and writers, and the interactions were also variable as they involved factors derived from the political and social situations, changes and development of the world order, affecting both Britain and the Ottoman Empire. About specific cases, further studies will be required on another occasions of research.
Keywords: Circadian rhythms.